Emerging biomaterials for downstream manufacturing of therapeutic proteins. (1st September 2019) - Li, Yi; Stern, David; Lock, Lye Lin; Mills, Jason; Ou, Shih-Hao; Morrow, Marina; Xu, Xuankuo; Ghose, Sanchayita; Li, Zheng Jian; Cui, Honggang
Graphical abstract: Abstract: Downstream processing is considered one of the most challenging phases of industrial manufacturing of therapeutic proteins, accounting for a large portion of the total production costs. The growing demand for therapeutic proteins in the biopharmaceutical market in addition to a significant rise in upstream titers have placed an increasing burden on the downstream purification process, which is often limited by high cost and insufficient capacities. To achieve efficient production and reduced costs, a variety of biomaterials have been exploited to improve the current techniques and also to develop superior alternatives. In this work, we discuss the significance of utilizing traditional biomaterials in downstream processing and review the recent progress in the development of new biomaterials for use in protein separation and purification. Several representative methods will be highlighted and discussed in detail, including affinity chromatography, non-affinity chromatography, membrane separations, magnetic separations, and precipitation/phase separations. Statement of Significance: Nowadays, downstream processing of therapeutic proteins is facing great challenges created by the rapid increase of the market size and upstream titers, starving for significant improvements or innovations in current downstream unit operations. Biomaterials have been widely used in downstream manufacturing of proteins and efforts have been continuously devoted to developing more advanced biomaterials for the implementation of more efficient and economical purification methods. This review covers recent advances in the development and application of biomaterials specifically exploited for various chromatographic and non-chromatographic techniques, highlighting several promising alternative strategies.